Optimisation of the distribution network mode by minimising active power losses in short-term planning - Tokhir F. Makhmudov; Adxam N. Ramatov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Due to the global increase in the share of renewable energy sources in the share of generation in distribution electric networks around the world, an acute problem of power fluctuations has arisen. Battery energy storage systems make it possible to smooth out peak loads, compensate for the instability of renewable energy generation, provide backup power and optimize network operation, including in the context of reducing total active power losses in the network. However, their implementation is associated with a number of technical, economic and regulatory challenges that require an integrated approach to integration and management. Aim: Selection of the connection node and power of the battery-based energy storage system in the distribution electrical network with a view to minimising active power losses in the network. Methods: The study used the Newton-Raphson method to calculate the steady state and total active power losses in the distribution network. When determining the capacities of the battery storage system, restrictions related to the balance of charge-discharge cycles were taken into account. An approach was applied involving a sequential change in the capacities of the storage system in order to determine the minimum active power losses. Results: An algorithm is presented that allows selecting the connection node of an energy storage system in terms of minimising active power losses. Using a test diagram of a distribution electrical network, the connection of a battery-based energy storage system was simulated, and the values of active power losses and the capacity of the battery-based energy storage system were obtained.